Retrograde intubation: An alternative way for the management of difficult airway - Lama, P; Shrestha, BR (Kathmandu University Medical Journal, 2009)
Inserting a retrograde wire into the pharynx through a cricothyroid puncture can facilitate tracheal intubation in difficult situations where either a flexible fiber-optic bronchoscope or an expert user of such a device is not available. Even in cases when fibropric can not be negotiated for the purpose,this method has been claimed to be useful to manage the airway. Some mouth opening is essential for the oral or nasal retrieval of the wire from the pharynx. Here, a case of post mandibular reconstructed wound infection required surgical debridement and plate removal from reconstructed lower mandible under general anesthesia. We retrieved the guide wire passed through a cricothyroid puncture and subsequently accomplished wire-guided oro-tracheal intubation. In the absence of a flexible fiber-optic bronchoscope, this technique is a very useful aid to intubate patients with limited mouth opening. Key words: cricothyrotomy, guide wire, retrograde endotracheal intubation (REI), surgery. doi: 10.3126/kumj.v6i4.1748 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 516-519